Konstruksi Hukum Pembiayaan Al Qardh Al Hasan Pada Bank Syariah (Studi Kasus Pada Bank Syariah Mandiri Cabang Yogyakarta) - Bagya Agung Prabowo (Jurnal Hukum IUS QUIA IUSTUM, 2005)
The legally binding of a collateral contract on the Al Qardh Al Hasan on The MandiriSyariah Bank in Yogyakarta indicates that the rules of Syariah does not regulate what kinds of collateral contracts. The procedure of collateral contract must be based on the rules of conventional law applied as apublic regulation which legally binding to all Syariah Bank in Indonesia.